From Brain Disease to Brain Health: Primary Prevention of Alzheimer’s Disease and Related Disorders in a Health System Using an Electronic Medical Record-Based Approach - Fosnacht, A.M. (J Prev Alzheimers Dis, 2017)
BACKGROUND: Alzheimer’s disease and aging brain disorders are progressive, often fatal neurodegenerative diseases. Successful aging, modern lifestyles and behaviors have combined to result in an expected epidemic. Risks for these diseases include genetic, medical, and lifestyle factors; over 20 modifiable risks have been reported. OBJECTIVES: We aim to primarily prevent Alzheimer’s disease and related disorders through electronic medical record (EMR)-based screening, risk assessments, interventions, and surveillance. DESIGN: We identified modifiable risks; developed human, systems and infrastructural resources; developed interventions; and targeted at-risk groups for the intervention. SETTING: A Community Based Health System. PARTICIPANTS: In year one (June 2015 to May 2016), 133 at-risk patients received brain health services with the goal of delaying or preventing Alzheimer’s disease and related disorders. MEASUREMENTS: We created mechanisms to identify patients at high risk of neurodegenerative disease; EMR-based structured clinical documentation support tools to evaluate risk factors and history; evidence-based interventions to modify risk; and the capacity for annual surveillance, pragmatic trials, and practice-based and genomic research using the EMR. RESULTS: This paper describes our Center for Brain Health, our EMR tools, and our first year of healthy but at-risk patients. CONCLUSION: We are translating research into primary prevention of Alzheimer’s disease and related disorders in our health system and aim to shift the paradigm in Neurology from brain disease to brain health.